Good Jew, bad Jew racism, anti-semitism and the assault on meaning - Friedman, Steven (Wits University Press, 2023)
Good Jew, Bad Jew is a critique by one of South Africa's foremost political theorists of mainstream understandings of Jewishness. Steven Friedman offers a searing analysis of the weaponisation of anti-Semitism in service of political objectives that support the Israeli state and global white supremacy. Looking specifically at the way in which language is used to shape identities, Friedman uses many examples to illustrate how anyone that opposes the interests and policies of the Israeli state is increasingly defined as anti-Semitic. The use of anti-racist language to defend racial domination distorts not only the meaning of what it is to be Jewish, but sheds light on how all dogmatic nationalisms function. Friedman uses India and South Africa as examples, but the analysis applies across the world too. This is a detailed, deeply researched and critical work that will appeal to both specialists and general readers looking for a considered view on how language shapes belief systems, and how the powerful forces of racism and nationalism - and their opponents - are being misrepresented. - "Political theorist Steven Friedman addresses how and why the current language around anti-Semitism in Israel has been distorted and weaponised to serve the political objectives of the Israeli state. Friedman's critique examines what this implies for the fight against racism in South Africa and India, and in other parts of the world."